HUBUNGAN TINGGI BADAN DENGAN PANJANG TANGAN PADA MAHASISWA FAKULTAS KEDOKTERAN UNSRAT ANGKATAN 2013 - Sambeka, Christanti; Tanudjaja, George N.; Pasiak, Taufiq F. (eBiomedik, 2015)
Abstract: Identification is important to the victims who have died, because identification is needed to know the person's identity. Body height can be determined using bones measurement, including metacarpal and phalanx. The purpose of this study is to find out the correlation of body height with hand length in the medical student of Sam Ratulangi University class of 2013. This study is an analytic descriptive study with design of cross-sectional study, and total participants of 72 students comprise of 36 male and 36 female. The samples of this study were chosen using the simple random sampling technique and were analyzed with the Pearson correlation analysis and also with the simple linear regression. The result showed a strong correlation between body heights and hand length with the value of ‘r’ in total was 0.855 in the whole subjects and 0.753 in male samples whereas in the female samples the value was 0.603. Based on the result of the simple linear regression analysis we get the formula of male body height = 15.496 + 8.398 x hand length, and the formula of female body height = 85.401 + 4.318 x hand length, and in total body heigth = 42.621 + 6.897 x hand length. Conclusion: There is a same direction and positive relationship between body height and hand length in the medical student of Sam Ratulangi University class of 2013.Keywords: identification, hand length, body height.Abstrak: Identifikasi sangatlah penting pada korban yang telah meninggal, karena identifikasi dilakukan untuk mengetahui kepastian identitas seseorang. Tinggi badan dapat ditentukan menggunakan ukuran tulang-tulang panjang, diantaranya tulang-tulang metakarpal dan tulang-tulang falang. Tujuan penelitian ini adalah untuk mengetahui hubungan antara tinggi badan dan panjang tangan pada mahasiswa Fakultas Kedokteraan Unsrat Angkatan 2013. Penelitian ini merupakan penelitian deskriptif analitik dengan rancangan cross-sectional, dengan sampel sejumlah 72 mahasiswa yang terdiri dari 36 mahasiswa laki-laki dan 36 mahasiswa perempuan. Sampel di pilih dengan menggunakan cara simple random sampling dan di analisis dengan analisis korelasi Pearson serta analisis regresi linier sederhana. Didapatkan hubungan yang kuat antara tinggi badan dengan panjang tangan dengan koefisien korelasi (r) pada keseluruhan subjek sebesar 0,855, sedangkan pada laki-laki 0,753 dan pada perempuan 0,603. Dari hasil analisis regresi linier sederhana di dapatkan rumus tinggi badan laki-laki = 15,496 + 8,398 x panjang tangan, tinggi badan perempuan = 85,401 + 4,318 x panjang tangan, dan secara keseluruhan tinggi badan = 42,621 + 6,897 x panjang tangan. Simpulan: Terdapat hubungan searah atau positif antara tinggi badan dengan panjang tangan pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi angkatan 2013.Kata kunci: identifikasi, panjang tangan, tinggi badan.